2003
DOI: 10.1091/mbc.e03-04-0228
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Folding-facilitating Mechanisms inTrypanosoma cruziEndoplasmic Reticulum

Abstract: Lectin (calreticulin [CRT])-N-glycan-mediated quality control of glycoprotein folding is operative in trypanosomatid protozoa but protein-linked monoglucosylated N-glycans are exclusively formed in these microorganisms by UDP-Glc:glycoprotein glucosyltransferase (GT)-dependent glucosylation. The gene coding for this enzyme in the human pathogen Trypanosoma cruzi was identified and sequenced. Even though several of this parasite glycoproteins have been identified as essential components of differentiation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 55 publications
3
45
0
Order By: Relevance
“…We were also able to successfully differentiate the null mutant into procyclic form T. brucei in vitro (data not shown), suggesting that the gene is also not required for differentiation to, or survival of the procyclic form of the parasite. In this regard, our results are similar to those of Parodi and co-workers (34,39), who have shown that, in the related American parasite T. cruzi, other components of the ER glucosylation-dependent quality control system (i.e. calreticulin and UGGT) can be deleted with only moderate effects on parasite growth, differentiation, and infectivity.…”
Section: Discussionsupporting
confidence: 92%
“…We were also able to successfully differentiate the null mutant into procyclic form T. brucei in vitro (data not shown), suggesting that the gene is also not required for differentiation to, or survival of the procyclic form of the parasite. In this regard, our results are similar to those of Parodi and co-workers (34,39), who have shown that, in the related American parasite T. cruzi, other components of the ER glucosylation-dependent quality control system (i.e. calreticulin and UGGT) can be deleted with only moderate effects on parasite growth, differentiation, and infectivity.…”
Section: Discussionsupporting
confidence: 92%
“…UGGTs that glucosylate N-glycans of misfolded proteins were demonstrated in three ways (7,8). First, genome project strains of Entamoeba and Trichomonas were grown and labeled with [2] 3 H-Man in the presence or absence of 200 g/ml of the glucosidase II inhibitor castanospermine (42).…”
Section: Methodsmentioning
confidence: 99%
“…UDP-Glc is also found in all three parasites and is the glucosyl donor for the unfolded glycoprotein glucosyltransferase (UGGT) involved in glycoprotein quality control in the endoplasmic reticulum (42,117). UGGT is known to function in all three parasites (17,51,68,80). UDP-Glc is also the presumed donor for the synthesis of base J (␤-D-glucosylhydroxymethyluracil), a rare deoxynucleotide found in telomere-proximal DNA in the bloodstream form of T. brucei and in the leishmania and T. cruzi (121).…”
Section: Cruzi) Gdp-man Is Also the Precursor Of Gdp-fuc (See Below)mentioning
confidence: 99%